2013
DOI: 10.1144/petgeo2011-083
|View full text |Cite
|
Sign up to set email alerts
|

Investigating reservoir pressure transmission for three types of coalbed methane reservoirs in the Qinshui Basin in Shan’xi Province, China

Abstract: Based on the characteristics of seven representative coalbed reservoirs in the Qinshui Basin in Shan’xi Province, China, the reservoirs were classified as gas pressure reservoirs, water pressure reservoirs or hybrid pressure reservoirs. Reservoir modelling technology was adopted to study the 1000 day recoverability and reservoir pressure transmission process of three typical coalbed methane (CBM) wells, each of which represents one of the three coalbed reservoir classifications identified. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Active water is used widely and frequently in hydraulic fracture and has lots of advantages of little damage, low price, wide supplement and mature technology (Zou et al 2013). If some nitrogen is added into active water, the suspension property and proppant carrying capacity will be increased obviously, and a better fracturing performance will be obtained (Hou et al 2017;Ranjith et al 2018).…”
Section: Fracture Fluid Typementioning
confidence: 99%
“…Active water is used widely and frequently in hydraulic fracture and has lots of advantages of little damage, low price, wide supplement and mature technology (Zou et al 2013). If some nitrogen is added into active water, the suspension property and proppant carrying capacity will be increased obviously, and a better fracturing performance will be obtained (Hou et al 2017;Ranjith et al 2018).…”
Section: Fracture Fluid Typementioning
confidence: 99%
“…The reservoir permeability represents the development degree of pores and fractures in coal seam and influences the degree of the gas flow in effective pores of the coal seam [23,33]. Permeability not only regulates the output efficiency of CBM but also affects the radius of the drainage and depressurization funnel in the CBM well [34]. Theory and practice have confirmed that permeability is one of the important reservoir indices for controlling CBM output [35,36].…”
Section: Index System Constructionmentioning
confidence: 99%
“…Because gas production is always undulate and relatively low in this stage, it is really hard to simulate. For this reason, simulators usually assume that there is no free gas in the reservoir (Wei and Zhang, 2010;Young, 1998;Zou et al, 2013aZou et al, , 2014. The assumption also exists in this study.…”
Section: Influence Radiusmentioning
confidence: 99%
“…Effective desorption radius is the distance from well bore to the place where reservoir pressure starts to decline down to the critical desorption pressure, which is influenced by influence radius, as detailedly defined and explained in Zou et al (2013a) and Sun et al (2017bSun et al ( , 2018d. During CBM drainage processes, drainages of water and gas lead to the increases of influence radius and effective desorption radius, as described in Figure 1.…”
Section: Effective Desorption Radiusmentioning
confidence: 99%
See 1 more Smart Citation